Impact of type 2 diabetes on postoperative outcome after hip fracture: nationwide population-based study in Taiwan. Issue 1 (20th February 2020) - Lee, Tien-Ching; Lee, Yu-Li; Chen, Jian-Chih; Chen, Chung-Hwan; Ho, Pei-Shan
Abstract : Summary: The impact of diabetes mellitus (DM) on hip fracture (HFx) is still controversial. We used nationwide population-based data in Taiwan to observe postoperative outcomes of HFx in patients with type 2 diabetes mellitus (T2DM) and found that the impact of T2DM may be related to medication of blood glucose control. Objective: Published studies evaluating diabetic patients with HFx have shown controversial outcomes. We assessed the impact of T2DM on postoperative outcomes after HFx in elderly patients using the nationwide population database in Taiwan. Research design and methods: We used data from the National Health Research Institute in Taiwan to recruit patients who had undergone operations for HFx between 2000 and 2009. The recruited patients with T2DM were divided into the oral antidiabetic drug (OAD) cohort and the insulin cohort according to the use or non-use of insulin. Patients without DM were propensity score matched in a 1:1 ratio by four variables. We used the χ 2 test, linear regression and Cox proportional hazards model to assess variables, including length of hospital stay, medical cost, complications, early readmission, and 1-year mortality. Results: We identified 5490 subjects in total. The insulin cohort exhibited prolonged hospital stay (11.8 days), higher medical costs, more complications within 30 and 90 after hip surgery, earlier readmission, and higher 1 year mortality rate (25.8%) than the OAD and non-DM cohorts. The OAD cohort had longer hospital stay (10.1 days) and higher readmission rate but fewer complications and mortality rates (14.9%) than the non-DM cohort. Conclusions: After matching confounding factors, the T2DM with OAD control groups were not associated with higher complication or mortality rates but were associated with higher readmission rates. However, diabetic patients with insulin control have poor outcome. The impact of T2DM on the postoperative outcomes of patients with HFx may be related to blood glucose control medication.